2019
DOI: 10.3390/cancers11081167
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL Induces Nuclear Translocation and Chromatin Localization of TRAIL Death Receptors

Abstract: Binding of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) to the plasma membrane TRAIL-R1/-R2 selectively kills tumor cells. This discovery led to evaluation of TRAIL-R1/-R2 as targets for anti-cancer therapy, yet the corresponding clinical trials were disappointing. Meanwhile, it emerged that many cancer cells are TRAIL-resistant and that TRAIL-R1/-R2-triggering may lead to tumor-promoting effects. Intriguingly, recent studies uncovered specific functions of long ignored intracellular TRAIL-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…This paradigm shift moved intracellular TRAIL receptors into the focus of current studies and resulted in the discovery of first cytoplasmic and nuclear functions of these receptors with nTRAIL-R2 being a regulator of miRNA maturation [ 18 , 40 – 42 ]. The subsequently reported presence of TRAIL death receptors in the chromatin fraction, signalized that this is just the beginning of the story about the nuclear functions of these proteins [ 12 ]. In agreement, here we propose that nTRAIL-R2 acts as an inhibitor of the tumor suppressor protein p53.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This paradigm shift moved intracellular TRAIL receptors into the focus of current studies and resulted in the discovery of first cytoplasmic and nuclear functions of these receptors with nTRAIL-R2 being a regulator of miRNA maturation [ 18 , 40 – 42 ]. The subsequently reported presence of TRAIL death receptors in the chromatin fraction, signalized that this is just the beginning of the story about the nuclear functions of these proteins [ 12 ]. In agreement, here we propose that nTRAIL-R2 acts as an inhibitor of the tumor suppressor protein p53.…”
Section: Discussionmentioning
confidence: 99%
“…All these TRAIL-R-functions are linked to their presence at the plasma membrane. Recently, it was shown that the TRAIL-Rs can translocate from the plasma membrane to the nucleus in TRAIL-dependent manner [ 12 ]. Interestingly, TRAIL-R1 and TRAIL-R2 are commonly overexpressed in cancer cells, but are frequently detected intracellularly and high intracellular abundance, especially of TRAIL-R2, was correlated with poor patient prognosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases, nuclear TRAIL-R localization has been reported to promote cell survival [ 200 ]. Recently, Mert and colleagues showed that both receptors can be endocytosed upon TRAIL binding by CME from the PM and undergo trafficking to the nucleus [ 201 ]. However, it is not clear how full-length DR4 and DR5 can enter the nucleus and exert their function in this compartment.…”
Section: Death Receptor Signaling From the Nucleusmentioning
confidence: 99%
“…Its protein product can speci cally kill cancer cells without harming normal cells [9][10][11][12][13]. Owing to its tumor cell-speci c killing effect, TRAIL has been widely used in preclinical and clinical studies [12,[14][15][16][17][18][19][20][21][22][23]]. In the current study, we used synthetic TRAIL-mRNA as an example to verify whether this method of intracranial injection can be applied for the treatment of GBM.…”
Section: Discussionmentioning
confidence: 99%